Classification of ≥80-year-old individuals into healthy, moderately healthy, and frail based on different frailty scores affects the interpretation of laboratory results - Edvardsson, Maria; Sund Levander, Märta; Milberg, Anna; Ernerudh, Jan; Wressle, Ewa; Marcusson, Jan; Grodzinsky, Ewa (Asian Journal of Medical Sciences, 2022)
Background: Interpretation laboratory analyses are crucial when assessing the patient’s condition. Reference intervals from apparently healthy and disease-free individuals may cause problems when outcomes from elderly patients with chronic diseases and on medications are being interpreted. Elderly individuals are a heterogeneous group ranging from individuals managing their daily life independently to individuals with diseases and impairment, in need of nursing care around the clock, that is, frail; a term widely used although there is no consensus on the definition. Aims and Objectives: The aim of the study was to study the effect of classification of elderly into healthy, moderately healthy, and frail, based on activities of daily living (ADL) and Mini-Mental State Examination (MMSE) or frailty index (FI), on the interpretation of outcomes regarding: Albumin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine, and gamma-glutamyltransferase (γ-GT) levels. Materials and Methods: Individuals ≥80 years (n=568) were classified either on ADL and MMSE or number of deficits, (FI). Results: Individuals classified as frail based on FI had lower mean levels for ALT, creatinine and γ-GT than individuals classified based on ADL and MMSE (P<0.05). Conclusion: The model to define health status to some extent affected laboratory analyte levels in ≥80 years old, classified as healthy, moderately healthy, and frail based on ADL and MMSE versus FI.